The Improvement of the Migration Legislation as a Factor of Optimization of the State Migration Policy of the Russian Federation - A. A. Khodusov (Сибирское юридическое обозрение, 2018)
The article discusses theoretical and practical issues of legislative regulation of migration processes in Russia. Migration policy and migration situation in Russia, the ratio of the norms of international law with the legal principles of our country, the problems of obtaining Russian citizenship, violation of the rights of refugees and internally displaced persons are analyzed. An inevitable and natural attribute of the globalization processes of today is the escalation of migration processes. Migration, emerging from the temporary and accidental phenomenon in the constant factor of strategic importance, is a vast resource, which is subject to effective use. Improvement of state migration policy, closely linking it to current problems of socio-economic development of the country, and everyday close attention to migration issues-these issues were determined by the President of the Russian Federation as extremely important.